Service and Computing Oriented Manufacturing: A Comprehensive Review - Tiwari, Bhupesh (Journal of Advanced Research in Service Management, 2023)
Service and Computing Oriented Manufacturing (SCOM) stands at the forefront of the manufacturing industry's evolution, representing a revolutionary approach that harnesses the power of cutting-edge technologies like the Internet of Things (IoT), Artificial Intelligence (AI), and Cloud Computing to redefine the core tenets of productivity, flexibility, and responsiveness in modern manufacturing processes. This comprehensive review embarks on an extensive journey into the world of SCOM, immersing itself in the foundational concepts, pivotal technologies, practical real-world applications, and the profound influence this emergent field exerts upon the contemporary manufacturing landscape. Rooted in a deep exploration of the historical trajectory of manufacturing paradigms and the pivotal role that SCOM plays within the framework of Industry 4.0, this review endeavors to offer a profound and holistic understanding of this transformative domain.